Community Perceptions of Plastic Waste Impacts at Viral Bagek Kembar Coastal Area: Persepsi Masyarakat terhadap Dampak Sampah Plastik di Kawasan Pesisir Viral Bagek Kembar - Mogan diah wari; Indayatun Aini; Erika Purnama Putri; Baiq Khusnul Murdiah; Asri Rahmatin; Dayang Nurfaizah (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2026)
Plastic waste accumulation in coastal areas threatens marine ecosystems, fisheries, and tourism sustainability. This study aimed to analyze community perceptions of plastic waste impacts at Viral Bagek Kembar Beach, Tanjung Karang Permai Village, Sekarbela District, Mataram City. A descriptive qualitative approach was applied through purposive sampling involving interviews with two key informants, namely a local RT head and a fisherman, conducted on May 26, 2026. Field observations were also carried out to document waste conditions along the shoreline. Results showed that plastic waste increases significantly during the rainy season due to sea currents and wind. Plastic materials, including bags, bottles, and food packaging, dominated the shoreline waste. Community perceptions indicated that plastic waste disrupts fishing activities by entangling gear, reduces coastal tourism aesthetics, and threatens marine biota. Waste management efforts such as routine beach clean-ups, community cooperation, and environmental awareness campaigns have been implemented by residents, students, and the local government. However, these efforts remain insufficient. In conclusion, community perceptions reflect a clear awareness of plastic waste impacts, yet management and environmental education need strengthening. Collaborative action among communities, government, and tourists is essential for sustainable coastal waste management.